Atividade de enzimas que hidrolisam nucleotídeos de adenina em plaquetas de pacientes com artrite reumatóide - Becker, Lara Vargas (2010)
Rheumatoid arthritis (RA) is a chronic inflammatory disease autoimmune of unknown etiology. Patients with RA have a lower survival than the general population, the most common cause of mortality in these patients is cardiovascular disease. The systemic inflammation that occurs in RA produces a spectrum of proatherogenic changes including endothelial dysfunction, insulin resistance, dyslipidemia, prothrombotic effects and pro-oxidative stress. Endothelial dysfunction is the key event in early atherogenesis. The platelets are known to have an important role in the maintenance of endothelial integrity and homeostasis, and also are key players in atherothrombosis. Extracellular adenine nucleotides ATP, ADP and AMP and the nucleoside adenosine, modulate a variety of tissue effects, exerting several effects on the platelets. This work determined the activity of enzymes involved in the degradation of nucleotides and nucleosides (NTPDase, 5 -nucleotidase E-NPP and ADA) in platelets from patients with RA and controls patients. It was selected thirty-five RA patients from the Hospital of the Federal University of Santa Maria and the diagnostic was based on the criteria of American College of Rheumatology. The results showed an increase in the activity of NTPDase (approximately 100%), 5 -nucleotidase (170%), E-NPP (approximately 100%) and ADA (approximately 45%) in the platelets of patients with RA when compared to control group. The increased activity of these enzymes could be related to a compensatory response of the organism due to the disease. The platelet aggregation was also determined in these patients and no changes were found when compared to the control group. The increase in ADA activity was lower when compared to the increase observed in the other enzymes activities (NTPDase, 5 -nucleotidase and ENPP). Possibly not all generated adenosine is converted by the ADA, which could explain the normality of platelet aggregation in patients with RA. No interference of the drugs (methotrexate, leflunomide,hydroxychloroquine and prednisone) utilized in RA treatment was observed on the enzymatic activities tested in vitro. In this way, it is possible to conclude that the NTPDase, 5 -nucleotidase, E-NPP and ADA activities are altered in platelets of patients with RA, which could be considered a compensatory response against the disease.